(untitled) (LACCEI, 2024)
This research is focused on evaluating the ergonomic risk factors associated with the handling of the manual pneumatic hammer in civil construction works by applying the Lest Method. With the application of the method in an initial way, it is determined that the most significant factors that affect the operators are the physical load (static and dynamic) and the physical environment (noise) with a rating of 10 "harmful situation" for said factors from a scale from 0-10. Twenty risks associated with the use of the hammer are identified, the most critical being pneumoconiosis, hearing loss, vascular and neurological diseases, and musculoskeletal disorders. To deal with it, controls were implemented such as the reduction of exposure time, the use of specific personal protective equipment to reduce vibration and noise, the optimization of the weight of the equipment, training for operators and the reduction of working hours. Applying the Lest method in a second stage, after the application of corrective measures, it is determined that the assessment of the significant risk factors is reduced approximately by half. It is concluded that this technique is useful for evaluating risk factors in construction activities by making a global diagnosis of multiple factors to which operators are exposed and determining those that are relevant. In addition, it allows determining the effectiveness of the implemented controls, determining that the controls reduced the level of occupational risk.